(untitled) (Research, Society and Development, 2020)
Objective: This study aimed to describe the functioning and performance of the multidisciplinary team of the program “better at home” in the municipality of Cristino Castro, Piauí, and to analyze the number of visits performed per year by the team. Methodology: This is a Reflexive and Observational Theoretical study, being developed mainly by analyzing the data provided by the coordination of the program “better at home” in the municipality of Cristino castro PI. Results: We analyzed data regarding the attendances made by the EMAD and EMAP team in 2017 and 2018, in the first year there were a total of 28 admissions made between the municipalities intercropped and in the second year of the program a total of 36 admissions to the program was made, it was still possible in 2017 to draw a profile of these patients being a total of 17 females and 11 males , ages ranged from 40 to 80 years, with only 1 patient younger than 15 years old. Conclusion: after the implementation of the program intercropped with neighboring municipalities, there was a look and care due to patients who don´t need an indication of hospitalization, where they were assisted only by Primary Care, overloading the care.